KEANEKARAGAMAN LUMUT DITAMAN NASIONAL BUKIT BARISAN SELATAN, PROVINSI LAMPUNG - Florentina Indah Windadri (BERITA BIOLOGI, 2010)
A survey on mosses diversity has been carried out in Bukit Barisan Selatan National Park at Lampung Province. Results of this study indicated that there are 37 species of mosses included in 3 genera and 11 families. Five species are considered as new records lo Sumatera i.e. Arthrocormus schimperi, Calymperes mountleyi, Fissidens perpusillus, Ectropotheciella distichophylla and Taxithelium lindbergii. Two species were suggested as new records to Indonesia i.e. Ectropothecium ferrugineum and Mnium laevinerve. While Ectropothecium ferrugineum is found in the research area, its endemic status is changed and the distribution area become more spreaded.